Pengembangan Sistem Pengelolaan Sampah Kawasan Wisata Pantai Kota Pariaman dengan Pendekatan Reduce-Reuse-Recycle - Rizki Aziz; Yommi Dewilda; Hafizhul Khair; Mikel Faklin (Fakultas Teknik, 2020)
The development of a reduce-reuse-recycle (3R) based solid waste management system was studied in the Pariaman City Beach Tourism Area which consists of Gandoriah Beach, Cermin Beach, Kata Beach, Angso Duo Island and Tangah Island. Solid waste managed is 2,646.813 m3/day. Development based on Permen PU No. 3 of 2013, with a scale of area management that serves 100% of the waste generated. The planned waste management system includes: sorting and storage, collection, processing at the Solid Waste Processing Site by Reduce Reuse Recycle approach (TPS3R) and transport to the landfill site. The needs of infrastructure and facility for solid waste management includes 100 liter of communal storage with three categories (compostable waste, recyclable waste and others) as many as 21 sets and 20 sets of communal storages as much as 4 sets. Waste collection uses indirect communal patterns with a 1.5 m3 motorized pedicab and one rattan basket 0.5 m3, processing at TPS 3R in by composting, grinding of coconut shell, making plastic handicrafts and selling recyclable plastic, paper and glass waste to third parties, transferring using a 6 m3 container followed by transportation from TPS 3R to Tungkal Selatan Landfill using arm roll truck.